Ecology, Community and Food Sovereignty: What's in a Word?. (1st December 2018) - Monaghan, Jade; Smith, Mick
Abstract : 'Food sovereignty' plays an increasingly important political role as a focus for grassroots agri-food organisations, such as La Via Campesina, in their attempts to contest the social injustices, health impacts and ecological damage resulting from the increasing global dominance of corporate/industrial agriculture. While not seeking to detract from the successes of such movements, there remain ethical, political and ecological concerns about just how the 'sovereignty' in food sovereignty is to be interpreted and what, if any, its relation to previous histories, definitions and applications of political sovereignty might be. Sovereignty's role, for example, in settler colonialism and environmental destruction is rarely addressed in the food sovereignty literature, with advocates focusing instead on its definitional malleability and contemporary political utility. Yet critical appropriations of Schmitt's infamous definition of sovereignty help to specify its colonial, anti-political and anti-ecological modus operandi, and make clear certain dangers inherent in uncritically adopting the term.